The Effectiveness of Inquiry-Based Learning with a Deep Learning Approach on Critical Thinking Skills of 8th Grade Junior High School Students - Habibi Salam; Rahayu Kariadinata; Muhammad Minan Chusni (Alpatih Harapan Semesta, 2025)
This research endeavors to evaluate the efficacy of implementing the Inquiry-Based Learning (IBL) model, augmented by a Deep Learning methodology, for the enhancement of critical thinking abilities and academic achievements in eighth-grade students at SMP Plus Al-Ittihad Cianjur, specifically concerning the human circulatory system. A quasi-experimental methodology, utilizing a one-group pretest-posttest framework, was adopted for this investigation. A cohort of 30 students was chosen via purposive sampling to constitute the study's sample. Data acquisition was performed utilizing pretest and posttest instruments, followed by analysis through descriptive statistical methods, the Shapiro–Wilk normality test, the Wilcoxon Signed Rank Test, and N-Gain analysis. The findings revealed a significant difference between pretest and posttest scores (Sig. 0.000 < 0.05). However, the average N-Gain score was 0.1311 or 13.11%, categorized as low and less effective. This indicates that although the IBL model with a Deep Learning approach has the potential to enhance critical thinking skills, its implementation has not yet been optimal. Contributing factors include students’ low readiness for active learning and teachers’ limited ability to facilitate reflective processes. Therefore, further teacher training and student engagement strategies are needed to maximize the effectiveness of this integrated approach in improving science learning quality in secondary education.